2007
DOI: 10.1038/sj.bjc.6603556
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional upregulation of human tissue kallikrein 6 in ovarian cancer: clinical and mechanistic aspects

Abstract: The human tissue kallikrein family (KLK for protein; KLK for gene) includes 15 members. Twelve kallikreins, including KLK6, are concurrently upregulated in ovarian cancer. However, the mechanism of this phenomenon remains unclear. In this study, we measured KLK6 expression in a large series of ovarian tissue cytosols and examined possible mechanisms of KLK6 up-regulation in ovarian cancer. Using a newly developed enzyme-linked immunosorbent assay (ELISA) with two monoclonal antibodies, we quantified KLK6 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
(51 reference statements)
2
34
0
3
Order By: Relevance
“…These results are similar to previous studies, which found increased KLK6 expression in ovarian cancers when compared to normal ovarian tissue (Anisowicz et al, 1996;Tanimoto et al, 2001;Ni et al, 2004). Interestingly, previous studies have also associated high KLK6 serum levels with advanced ovarian cancer (stage III/IV) and serous tumour histology (Hoffman et al, 2002;Shan et al, 2007). Ovarian serous tumours of borderline and low grade are thought to arise from a step-wise progression from adenoma to borderline tumour to carcinoma through the Ras-Raf signalling pathway (Bell, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to previous studies, which found increased KLK6 expression in ovarian cancers when compared to normal ovarian tissue (Anisowicz et al, 1996;Tanimoto et al, 2001;Ni et al, 2004). Interestingly, previous studies have also associated high KLK6 serum levels with advanced ovarian cancer (stage III/IV) and serous tumour histology (Hoffman et al, 2002;Shan et al, 2007). Ovarian serous tumours of borderline and low grade are thought to arise from a step-wise progression from adenoma to borderline tumour to carcinoma through the Ras-Raf signalling pathway (Bell, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Hormonal control is another postulated mechanism (Yousef and Diamandis, 1999;Shaw and Diamandis, 2008;Lai et al, 2009). However, there are also reports that suggest that other regulatory mechanism exists for KLK expression in cancers (Shan et al, 2007). Our findings highlight the possibility that miRNAs represent a potential regulatory mechanism for controlling kallikrein expression at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 62%
“…Assessment of KLK protein dysregulation in ovarian cancer was compiled from the results of 17 studies (Dong et al, 2001;Luo et al, 2001Luo et al, , 2003Tanimoto et al, 2001;Hoffman et al, 2002;Yousef et al, , 2003bBorgono et al, 2003;Diamandis et al, 2003;Ni et al, 2004;Scorilas et al, 2004;Xi et al, 2004;Prezas et al, 2006;Shan et al, 2007;Bayani et al, 2008;Shaw and Diamandis, 2008). Chromosomal aberration in ovarian cancer was extracted from the Progenetix comparative genomic hybridisation database available as of January 2009 (Baudis and Cleary, 2001).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Ovarian cancer cells that either constitutively overexpress active Akt/AKT1 or exhibit AKT2 gene amplification are highly resistant to paclitaxel compared with cells with low AKT levels 23. Overexpression of KLK6 24, EGFR 25, LMX1B 26, BMP8B and ATP13A4 27, because of gene amplification or high copy number gains, is associated with worse PFS and OS in patients with ovarian cancer. In contrast, an increased copy number of GAB2 is associated with improved PFS and OS and correlates with enhanced sensitivity to the dual PI3K/mTOR inhibitor PF‐04691502 in vitro 27.…”
Section: Molecular Portraits Underlying Th Of Eocmentioning
confidence: 99%